Color Doppler Imaging Analysis of Ocular Blood Flow Velocities in Normal Tension Glaucoma Patients: A Meta-Analysis - Shuo Xu; Shouyue Huang; Zhongjing Lin; Wangmin Liu; Yisheng Zhong (Journal of Ophthalmology)
Background. To evaluate the potential diagnostic value of CDI of retrobulbar hemodynamic changes in NTG patients. Methods. Relevant publications which included PSV, EDV, and RI of OA, CRA, NPCA, and TPCA in NTG patients and normal controls measured by CDI were retrieved from the Cochrane Central Register of Controlled Trials, PubMed, the ISI Web of Knowledge, and EMBASE from 1990 to 2014. Subgroup analyses were made based on IOP-lowering medications uses. Result. In OA, there was significant decrease of PSV with moderate heterogeneity (P<0.00001, I2=49%) and significant decrease of EDV with significant heterogeneity (P=0.0005, I2=87%) in NTG patients. In CRA, similar results of PSV (P<0.00001, I2=42%) and EDV (P<0.00001, I2=80%) were detected. Significant decrease of PSV and EDV with significant heterogeneity was also found in both NPCA (P<0.0001, I2=70%; P<0.0001, I2=76%; resp.) and TPCA (P<0.00001, I2=54%; P<0.00001, I2=65%; resp.). Statistically significant increases of RI were found in CRA (P=0.0002, I2=89%) and TPCA (P=0.02, I2=81%) with significant heterogeneities, though RI in OA (P=0.25, I2=94%) and in NPCA (P=0.15, I2=86%) showed no statistical changes with significant heterogeneities. Conclusions. Ischemic change of retrobulbar hemodynamics is one of the important manifestations of NTG. Hemodynamic parameters measured by CDI might be potential diagnostic tools for NTG.